1971
DOI: 10.1021/jo00815a017
|View full text |Cite
|
Sign up to set email alerts
|

Biimidazole-sensitized photooxidation of leuco triphenylmethane dyes

Abstract: Acknowledgments. -The authors wish to express their appreciRtion to R, Dessauer, L. Cescon, and c.Yembrick for bringing the present problem to their attention and for supplying most of the compounds used in this study. The aid of J. M. White in carrying out these experiments is gratefully acknowledged.We also thank v. I?. Hanson for the construction of the flash photolysis apparatus and €3. R. Stevens for assistance.The oxidation of tris(2-1iiethyl-4-diethyla1ni1iophenyl)iiietha~~e by photogenerated 2-(o-chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The high stability of the trityl cation in polymer Ic may be contributed to the extensive delocalization of the charge onto the phenyl rings and TPA via resonance as shown in Scheme . The halocarbon‐sensitized photooxidation mechanism of triphenylmethane have already be described 40, 41. The new absorption band at 698 nm of Ic in Figure 11(b) is another strong evidence that the methine protons of TPA derivatives‐benzaldehyde polymers could be completely eliminated by UV light, which Sato also reported the similar absorption result by the reaction of polymer Ib with oxidant 42…”
Section: Resultssupporting
confidence: 52%
“…The high stability of the trityl cation in polymer Ic may be contributed to the extensive delocalization of the charge onto the phenyl rings and TPA via resonance as shown in Scheme . The halocarbon‐sensitized photooxidation mechanism of triphenylmethane have already be described 40, 41. The new absorption band at 698 nm of Ic in Figure 11(b) is another strong evidence that the methine protons of TPA derivatives‐benzaldehyde polymers could be completely eliminated by UV light, which Sato also reported the similar absorption result by the reaction of polymer Ib with oxidant 42…”
Section: Resultssupporting
confidence: 52%
“…5. With 2,6-Di-iert-butylphenol (9).-A solution prepared in the dark from 1.3 g of 9, 1.5 g of biimidazole lb, and 100 ml of benzene was irradiated 1 hr, 6 in. from a sun lamp.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of representative reactions are the subject of mechanistic studies reported in subsequent papers. [9][10][11][12][13] Radicals 2 do not react with aromatic hydrocarbons, aliphatic alcohols, oxygen, or vinyl monomers at rates which compete detectably with dimerization or the oxidation reactions studied. Thus, benzene and methanol could be used as solvents under conditions employed without observing side products due to their presence.…”
mentioning
confidence: 99%
“…[29][30][31][32] The mechanism of the bisimidazole-sensitized photooxidation of leuco Crystal Violet has been studied. 33 The first step of the reaction involves an electronexchange reaction between 2-(o-chlorophenyl)-4,5-diphenylimidazolyl radical 18 (generated from the corresponding dimer) and the leuco dye, forming a solvated electron and a radical cation 26,34,35 19. Decay of the radical cation results in the formation of a dye cation 20 and a hydrogen atom.…”
Section: Via Oxidationmentioning
confidence: 99%